2022
DOI: 10.1177/23333936221109876
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Clinical Decision-Making in a Changed COVID-19 Work Environment: A Focus Group Study

Abstract: This study aims to explore how a changed COVID-19 work environment influences nurses’ clinical decision-making. Data were collected via three focus groups totaling 14 nurses working in COVID-19 pandemic wards at a Danish university hospital. The factors influencing decision-making are described in three themes; navigating in a COVID-19 dominated context, recognizing the importance of collegial fellowship, and the complexities of feeling competent. A strong joint commitment among the nurses to manage critical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…A study found that healthcare professionals feel their hospitals must prepare for pandemics and are not involved in decision-making. Involving employees in decision-making and preparation processes is crucial for maintaining morale and quality of care during such events [42]. It is essential to create supportive and inclusive work environments that recognize the critical role of healthcare professionals in managing the healthcare system during a pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that healthcare professionals feel their hospitals must prepare for pandemics and are not involved in decision-making. Involving employees in decision-making and preparation processes is crucial for maintaining morale and quality of care during such events [42]. It is essential to create supportive and inclusive work environments that recognize the critical role of healthcare professionals in managing the healthcare system during a pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…15 Interview methods were used to collect data in most of the qualitative studies. [7][8][9]11,12,24,46,56,[63][64][65][66][67] Written data 64 and observations were also used. 7,65 Surveys were used to carry out the quantitative studies.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…For example, it has been used to describe nurses' inter-professional collaborations with physicians 25,53,54 and nursing educators 55 and those working in the social care sector. 48 The aim of inter-professional collegiality has been to promote communication, facilitate decision-making, 52,55,56 achieve mutual learning, share knowledge sharing 48,56 and enable collegial mentoring. 25,48,56 It has been seen as a strategy to support a united and safe working culture 48 and ethics among professionals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPDM was presented in the context of research on decision-making in acute care nursing and responds to the peculiarities of this setting—such as the need to consider numerous potentially conflicting factors 16 and make numerous decisions under temporal pressure. Situations like the COVID-19 pandemic add elements to the equation, such as the relocation of nurses to wards that are outside their field of expertise 17 , perception of physicians’ lack of knowledge, precariousness of the facilities, or lack of information about the patients as they were admitted without accompanying relatives 18 .…”
Section: Introductionmentioning
confidence: 99%